Pola Bimbingan Penyuluhan Remaja dalam Menangani Fenomena Bermain Layang-layang Beresiko (Studi Kasus di Jalan Lintas Selatan Srigading Sanden Bantul Yogyakarta) - Bagus Mahardika (Ikhtisar: Jurnal Pengetahuan Islam, 2024)
Adolescence is a period of transition from childhood to adulthood, where during this period a very large sensitivity to curiosity grows, hormonal growth and development in teenagers causes them to enjoy various activities, including activities with negative value such as the increasing trend of flying kites. It often happens on the southern route, even though the hot weather doesn't deter teenagers who are just starting to get involved in the game, they don't pay attention to the risks and dangers. The aim of this research is to find out how youth counseling is provided in handling cases of risky kite flying on the southern highway. The research method that the researcher used was a type of qualitative research with a case study approach where the researcher wanted to dig deeper into information related to the risky phenomenon of kite flying and efforts to overcome it through counseling. The results of the research show that playing with kites is risky for teenagers to fill free time, they are bored at home and want to look for new activities, the counseling guidance pattern for teenagers is carried out by involving community leaders, namely the head of the local hamlet and RT, in providing understanding to teenagers assisted by LIMAS. regarding the dangers of flying a kite, it is risky, especially if the wind is strong, when it rains there is a risk of being struck by lightning and the size of a super large kite will be dangerous because it can drag someone who is playing, causing them to fall and suffer broken bones, not to mention if the kite gets caught. The risk of being hit by an electric pole is increasingly fatal. Through counseling carried out in groups, it is hoped that teenagers will have the awareness to always obey what is advised so that they can play safely and not endanger themselves or others. Keywords: Counseling, risky kite flying, teenagers